3D virtual reconstruction of seven scenes from the Tulunid lost city in Egypt - Ibrahim Elassal; Andrea Chávez Triviño; Iván Darío Chávez Triviño (Virtual Archaeology Review)
Reviving both the tangible and intangible aspects of lost heritage is essential to preserve awareness for future generations. The 9th-century city of Al-Qaṭāʾi in Egypt has been repeatedly destroyed during the conflicts between the Tulunids and the Abbasids. Virtual technologies and three-dimensional (3D) reconstruction serve to digitally raise awareness of the city and its historical significance, especially since it no longer exists. The challenge of digital revival in this project's framework is to imagine how life unfolded in the city during the 9th century. Our goal in this project is to leverage the advancements in 3D modelling technologies to reconstruct the lost historical Egyptian city. The methodology report begins with a description of the foundation for the 3D model reconstruction of the historically lost city, which serves as the main case study for this project. The methodology for this reconstruction is achieved through scope definition, wherein the main structures and complementary elements of the scene are identified. This is followed by the documentation phase, during which all available information on the scene is gathered through sketches, engravings, photographs, plans, and other sources. The next phase involves establishing hypotheses, where 2D and 3D sketches are produced to propose the general volumes of structures and elements. Finally, the creation of 3D models brings the structures and associated elements to life through the texturing process, as well as the inclusion of terrain, vegetation, fauna, characters, and other components, allowing the complete scene to emerge. The objective of the article is to revive the destroyed architecture of the non-existent city and communicate its value to the public through interactive virtual exploration. This study aims to demonstrate how the combination of digital methods for virtual reconstruction is valuable for both knowledge dissemination and research, through the case study of Al-Qaṭāʾi in Egypt.